The Process and Effect of Demographic Transition in Penang, Malaysia - Usman Haji Yaakob,; Nik Norliati Fitri Md Nor, (Kajian Malaysia, 2013)
This article describes the demographic transition in Penang, Malaysia based on the demographic transition theory, which explains the decline of birth and death rates in European countries during the 18th century. It has been noted that the birth and death rates in Penang decreased by more than 62% between 1950 and 2009, although the standard of living increased. The decline in birth and death rates, including infant mortality, and the improvement in the standard of living may be associated with rapid urbanisation, industrialisation and modernisation. The decline in birth and death rates is associated with the opportunities for women to become highly educated and participate in the labour force, particularly in the industrial sector. This has resulted in delayed first marriages and an increase in the proportion of unmarried women who are age 30 or older. These trends have clearly affected the fertility rate in Penang, which was below 2.1 and 1.8 children per couple in 2001 and 2009, respectively. As a developed state, Penang currently has an aging population with 10.2% of its residents being older than 60. This article concludes that the problem of an aging population cannot be avoided and will characterise Penang in the coming years.